2020
DOI: 10.1002/cpt.2082
|View full text |Cite
|
Sign up to set email alerts
|

Inosine 5'‐Monophosphate to Raise Serum Uric Acid Level in Multiple System Atrophy (IMPROVE‐MSA study)

Abstract: The aim of this trial was to investigate the safety, tolerability, and capability of serum uric acid (UA) elevation of inosine 5'‐monophosphate (IMP) in multiple system atrophy (MSA). The IMPROVE‐MSA trial was a randomized, double‐blind, placebo‐controlled trial in patients with MSA with no history of hyperuricemia‐related disorders. The participants were assigned to placebo (n = 25) or IMP (n = 30) in a 1 to 1 ratio, and then followed up for 24 weeks. The primary end points included safety, tolerability, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…1. After the application of our search strategy, we found that eleven RCTs [9][10][11][12][13][14][15][16][17][18][19] published between 1996 and 2021, that met our selection criteria. The included RCTs have a JADAD score of 4 or greater.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. After the application of our search strategy, we found that eleven RCTs [9][10][11][12][13][14][15][16][17][18][19] published between 1996 and 2021, that met our selection criteria. The included RCTs have a JADAD score of 4 or greater.…”
Section: Resultsmentioning
confidence: 99%
“…Only eight of the studies [10,11,[14][15][16][17][18][19] reported in detail the exact number of patients experiencing at least one AE in the study groups. The pooled estimate of the percentage of placebo treated patients with at least one AE was 64.2% (95% CI = 43.2-82.6%), compared to 72.4% (95% CI = 53.4-88.0%) for active drug treated patients.…”
Section: Adverse Events In Placebo and Active Drug Armmentioning
confidence: 99%
“…However, another recent clinical trial showed that inosine treatment does not modify progression of early Parkinson’s disease ( Schwarzschild et al, 2021 ). In a clinical trial for use of IMP in multiple system atrophy (MSA), IMP raised serum levels of uric acids, and was considered to be tolerable and safe during a 24-week treatment ( Jung Lee et al, 2021 ), although a more long-term follow-up study is warranted.…”
Section: Inosine and Other Diseasesmentioning
confidence: 99%